Moral Integrity Guru sebagai Determinan Pengelolaan Kelas Efektif di Lingkungan Pesantren - Faisal Faisal (CV. Laskar Karya, 2025)
Classroom management is a crucial aspect of learning effectiveness, especially within pesantren environments that possess distinctive cultural and spiritual characteristics. This study aims to analyze the role of teachers’ moral integrity as a determinant of effective classroom management by comparing the figures of Kyai and Non-Kyai in the Jalaluddin Ar-Rumi Region of Nurul Jadid Islamic Boarding School. The research adopts a qualitative approach using a case study method. The research subjects consist of regional teachers, tarbiyah administrators, and students. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis employed the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings reveal that Kyai, with strong moral and symbolic authority, are able to create an orderly classroom atmosphere without relying on verbal control or punishment. Conversely, Non-Kyai teachers face serious challenges in establishing discipline and student engagement due to their weak moral legitimacy. The novelty of this research lies in its value-based managerial approach that positions moral integrity as a key element of classroom leadership. These findings imply that the regional management system should place moral integrity as a primary indicator in teacher development and evaluation.